Expression of Luteinizing Hormone Receptor in the Gastrointestinal Tract in Patients with and without Dysmotility - Oskar Hammar; Béla Veress; Agneta Montgomery; Bodil Ohlsson (AboutScience Srl, 2012)
Leuprolide is a gonadotropin-releasing hormone (GnRH) analog which has been shown to reduce symptoms in patients with irritable bowel syndrome (IBS) and chronic intestinal pseudo-obstruction (CIPO). The mechanism is not known, but one hypothesis is through down-modulation of luteinizing hormone (LH) secretion, a hormone whith antagonistic effect on gastrointestinal motility. However, presence of LH receptors in the gastrointestinal tract has never been described. The aim of this study was to find one possible way of action for leuprolide by examining the presence of the LH receptor, and if present, to see whether there was different expression in patients with or without dysmotility. Full-thickness biopsies from the bowel wall of patients with and without severe dysmotility were examined using immunohistochemistry staining. Biopsies showed expression of LH receptors on myenteric neurons and in glial cells, neutrophils, endothelial cells and mast cells. There was no difference in expression between patient groups.